2010
DOI: 10.1183/09031936.00117509
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Control Questionnaire in children: validation, measurement properties, interpretation

Abstract: The Asthma Control Questionnaire (ACQ) has been validated in adults to measure the primary goal of management (minimisation of symptoms, activity limitations, short-acting b 2 -agonist use and airway narrowing). The present study evaluated the validity, measurement properties and interpretability of the ACQ in children aged 6-16 yrs.35 children attended clinic on three occasions (0, 1 and 4 weeks) and completed the ACQ, Mini Paediatric Asthma Quality of Life Questionnaire and the Royal College of Physicians' '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
219
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(229 citation statements)
references
References 21 publications
4
219
0
6
Order By: Relevance
“…This measure has been validated for asthma symptom change in adults (reliability = 0.90) 36 and children (reliability = 0.79). 42 We asked parents to report on symptoms, with the child available to consult. Lower scores indicate less impairment.…”
Section: Methodsmentioning
confidence: 99%
“…This measure has been validated for asthma symptom change in adults (reliability = 0.90) 36 and children (reliability = 0.79). 42 We asked parents to report on symptoms, with the child available to consult. Lower scores indicate less impairment.…”
Section: Methodsmentioning
confidence: 99%
“…58 For the children's version, a similar minimum clinically important difference was reported (0.52) in the initial validation study with a sample of 35 children. 53 However, a study with a larger sample size (n ϭ 305) reported a change of 0.40 as the minimum clinically important difference among children. 54 …”
Section: Responsivenessmentioning
confidence: 99%
“…However, a trained interviewer is required to administer the questionnaire to children 6 -10 y old. 53,54 …”
Section: Asthma Control Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…21 Several tools for assessing asthma control have been developed, but few have been validated for ongoing monitoring, and studies have reported significant limitations in children. [22][23][24][25][26][27] We have developed a new tool, the Asthma Symptom Tracker (AST) or Asthma…”
Section: Discussionmentioning
confidence: 99%